CHARACTERIZATION IN A FAIRY TALE ENTITLEDJACK AND THE BEANSTALK:A Critical Discourse Analysis on Two Versions of Jack and the Beanstalk - Dyah Agustine, - (2011)
Since most people often take fairy tales for granted, it is significant to conduct a research that analyzes this kind of literary works. Not only it makes people appreciate fairy tales more, it also gives a contribution to children's education. This research paper presents a Critical Discourse Analysis on two versions of a fairy tale entitled Jack and the Beanstalk. One version is written by Andrew Lang, a Scottish, and the other is written by Joseph Jacobs, a Jewish. Employing Leeuwen's (1996) representation of social actors as its analysis framework, this study focuses on the characterization in the two versions; how the characters are presented, what are the similarities and differences and what are the ideologies reflected in the characterization. Leeuwen proposes ten categories for this social actors' representation. The analysis finds that both authors present the protagonist and antagonist as important characters, but Lang presents the protagonist as having positives qualities and the antagonist as having negative qualities while Jacobs does not.This study concludes that through characterization, Lang focuses more on the importance of family relation, while Jacobs focuses more on the issue of rich and poor. It shows that Lang version, of which characterization is more specific, detailed and obvious about the good and evil, makes the readers able to grasp the moral values of the story more easily, while Jacobs version, of which characterization blurs the boundary line between good and evil, makes the moral values grasping more difficult.